Unraveling Gender Influences on Students' Attitudes in Physics Education - Dahal, Bishnu Kumar (Teacher Half-Yearly Journal, 2025)
This study examines the subtle effect of bachelor-level students' attitudes toward physics education from gender perspectives in constituent education campuses affiliated with Tribhuvan University. A cross-sectional survey approach was employed to collect data from a sample of 71 participants, consisting of 23 males and 48 females. A five-point Likert scale was the primary tool for data collection. The enquiry focused on students' perceptions of physics education, capturing their current attitudes and views at a specific moment in time. The research aimed to assess the nuanced influences of gender on different perspectives related to enthusiasm for physics, perceptions of physics as a dynamic process, and satisfaction with subject teachers’ attributes. The findings showed robust enthusiasm, contentment with learning, and positive attitudes toward physics were observed, with satisfaction in class responses, engagement in lab work, and active problem-solving practices in both male and female students, offering valuable insights for promoting inclusivity and improving teaching methodologies in physics education. In the realm of physics learning.